The Dilemma of Off-Campus Accommodation among Students of University of Jos: Implications for Campus Hostel Management - Orinya, C. O.; Mazadu, A. A.; Kassai, M. N. (International Journal of Real Estate, 2025)
Inadequate hostels in tertiary institutions creates force choice between on-campus and off-campus residence. Students that cannot access on-campus hostels, reside off-campus. Residing off-campus exposes students to kidnaping and death from incessant crisis of which students have fallen victims. In view of these problems, this study is undertaken to ascertain students’ choice of residence, identify influencers of students’ choice of residence and measures of encouraging on-campus residence. The research findings shown that 45.6% of the students reside on-campus while 54.4% reside off-campus. 46.7% preferred on-campus residence and 53.3% preferred off-campus residence. Major reasons for the preference of on-campus residence are easy access to institution’s facilities, availability of water and electricity, low cost of accommodation while privacy, comfort and convenience are for off-campus residence. Topmost influencers are security, hygiene, quality facilities and services, proximity to lecture venue. ‘Avoiding leaving accommodation every session’ is found as new influencer, constituting an addition to knowledge. Topmost measures for making on-campus residence preferable are regular water and electricity supply, security, hostels renovation, effective management and maintenance practice.